2015
DOI: 10.1186/s13104-015-1332-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with anaesthesia services and associated factors at the University of Gondar Hospital, 2013: a cross-sectional study

Abstract: BackgroundPatient satisfaction is the degree of fulfilling patients’ anticipation which is an important component and quality indicator in anaesthesia service. It can be affected by anaesthetist patient interaction, perioperative anaesthetic management and postoperative follow up. No previous study conducted in our setup. The aim was to assess patient satisfaction with anaesthesia services and associated factors.MethodsInstitutional based cross sectional study was conducted from April 15–30, 2013 at the Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
4
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 20 publications
(20 reference statements)
4
29
4
4
Order By: Relevance
“…We report a low dissatisfaction rate with our glaucoma service of ~8% in our population. Dissatisfaction rates of patients with other chronic diseases such as type 2 diabetes, 8 , 9 , 25 ischemic heart disease, 26 chronic obstructive lung disease, 26 and with anesthetic practices 27 have higher rates of dissatisfaction ranging from 20% to 30%. From our study, understanding of glaucoma test results, complications, and disease management scored higher dissatisfaction rates compared with the areas of patient time spent per consultation with clinician and patient–clinician rapport.…”
Section: Discussionmentioning
confidence: 99%
“…We report a low dissatisfaction rate with our glaucoma service of ~8% in our population. Dissatisfaction rates of patients with other chronic diseases such as type 2 diabetes, 8 , 9 , 25 ischemic heart disease, 26 chronic obstructive lung disease, 26 and with anesthetic practices 27 have higher rates of dissatisfaction ranging from 20% to 30%. From our study, understanding of glaucoma test results, complications, and disease management scored higher dissatisfaction rates compared with the areas of patient time spent per consultation with clinician and patient–clinician rapport.…”
Section: Discussionmentioning
confidence: 99%
“…Other hospital satisfaction surveys have reported that satisfaction rates in anaesthesia is >85%. 8,10,[11][12][13][14] In our study only 76% of patients who experienced GA were satisfied whereas 100% of patients satisfied with SCBPB. But it is not absolute satisfaction, rather relative satisfaction to another group.…”
Section: Discussionmentioning
confidence: 78%
“…Nakahashi K et al 7 found more patients satisfied in GA in comparison to regional anaesthesia. Endale Gebreegziabher Gebremedhn et al 8 in their study found out of 111 patients who were managed under general anaesthesia, 97 (87.4%) were satisfied and 14 (12.6%) dissatisfied. Whereas out of 45 regional cases, 44 (97.8%) were satisfied and 1 (2.2%) dissatisfied (GA vs. RA, P = 0.046).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many factors contribute to patient satisfaction including accessibility and convenience of services, interpersonal relationships, competence of health professionals and patient expectations and preferences. 4 Therefore we undertook a survey to analyse patient perception of communication and their satisfaction with the communication practices at pre anaesthetic evaluation clinic (PAC) of a tertiary care hospital in India.…”
Section: Introductionmentioning
confidence: 99%